Essence and practice of oral history (Tempo e Argumento, 2012)
This article/lecture discusses the relationship among history, oral history, and history of today. It states that the cleavage among them is not fixed but they integrate each other to the point that their boundaries are blurred. Moreover, since the moment that oral history is presented as a historical science’s sub-branch; it is discussed whether the Latin American characteristics can mean the existence of a specifically "Latin American" oral history.
Keywords: history; orality; Latin America; history practices